Gold nanoparticles: current and upcoming biomedical applications in sensing, drug, and gene delivery. Issue 78 (12th September 2022) - Yañez-Aulestia, Ana; Gupta, Nishesh Kumar; Hernández, Magali; Osorio-Toribio, Génesis; Sánchez-González, Elí; Guzmán-Vargas, Ariel; Rivera, José L.; Ibarra, Ilich A.; Lima, Enrique
Abstract : Gold nanoparticles present unique physicochemical characteristics, low cytotoxicity, chemical stability, size/morphology tunability, surface functionalization capability, and optical properties which can be exploited for detection applications. Abstract : Gold nanoparticles (AuNPs) present unique physicochemical characteristics, low cytotoxicity, chemical stability, size/morphology tunability, surface functionalization capability, and optical properties which can be exploited for detection applications (colorimetry, surface-enhanced Raman scattering, and photoluminescence). The current challenge for AuNPs is incorporating these properties in developing more sensible and selective sensing methods and multifunctional platforms capable of controlled and precise drug or gene delivery. This review briefly highlights the recent progress of AuNPs in biomedicine as bio-sensors and targeted nano vehicles.